Practical and Judicial Applications of Civil Liability in the Medical Partnership Contract - Ahmed, Mariwan Salih; Al-Hadithi, Ali Salah (Journal of Posthumanism, 2025)
Identifying and cataloging medical errors is nearly impossible due to their abundance and diversity, stemming from the ever-evolving nature of the medical profession whether in terms of scientific theories, treatment methods, or the medical devices and tools used. Therefore, this research aims to explore certain practical applications of medical error committed by physicians within the framework of a medical partnership contract, as such cases are among the most common and widespread in medical practice. The study seeks to examine, contextualize, and analyze these instances from various legal perspectives.